Dual-energy CT: radiation dose aspects - Henzler, Thomas; Fink, Christian; Schönberg, Stefan (American journal of roentgenology, 2012)
Objective: Various applications for dual-energy CT (DECT) have been investigated and have shown substantial clinical benefits. However, only limited data are available regarding the radiation dose associated with DECT imaging. The purpose of this article is to review the available literature regarding the radiation dose associated with DECT imaging applications in comparison with conventional single-energy CT techniques. Conclusion: The rediscovery of DECT and the increasing availability of this technique on clinical CT systems have opened new dimensions for CT. The advanced spectral differentiation of materials within the human body as well as the selective visualization or subtraction of iodinated contrast material or xenon provides both advanced visualization of disease-specific molecular substrates as well as additional functional information within a single scan.